2015
DOI: 10.1016/j.nimb.2014.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale calculations of dislocation bias in fcc Ni and bcc Fe model lattices

Abstract: a b s t r a c tIn order to gain more insights on void swelling, dislocation bias is studied in this work. Molecular static simulations with empirical potentials are applied to map the dislocation-point defects interaction energies in both fcc Ni and bcc Fe model lattices. The interaction energies are then used to numerically solve the diffusion equation and obtain the dislocation bias. The importance of the dislocation core region is studied under a the temperature range 573-1173 K and the dislocation densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The nature of dislocation loops, e.g., interstitial type or vacancy type, as well as their Burgers vectors, is the key factor for the microstructure evolution of irradiation damage. The bias effect of dislocation loops on point defects would influence irradiation swelling of materials [7]. Gao et al [8] experimentally demonstrated that the bias factor of interstitial-type loops was higher than that of vacancytype loops.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of dislocation loops, e.g., interstitial type or vacancy type, as well as their Burgers vectors, is the key factor for the microstructure evolution of irradiation damage. The bias effect of dislocation loops on point defects would influence irradiation swelling of materials [7]. Gao et al [8] experimentally demonstrated that the bias factor of interstitial-type loops was higher than that of vacancytype loops.…”
Section: Introductionmentioning
confidence: 99%